Infant feeding experiences and concerns among caregivers early in the COVID‐19 State of Emergency in Nova Scotia, Canada - Hillary L. Fry; Olga Levin; Ksenia Kholina; Jolene L. Bianco; Jelisa Gallant; Kathleen Chan; Kyly C. Whitfield (Wiley, 2021)
Abstract The global emergency caused by the novel coronavirus (COVID‐19) pandemic has impacted access to goods and services such as health care and social supports, but the impact on infant feeding remains unclear. Thus, the objective of this study was to explore how caregivers of infants under 6 months of age perceived changes to infant feeding and other food and health‐related matters during the COVID‐19 State of Emergency in Nova Scotia, Canada. Four weeks after the State of Emergency began, between 17 April and 15 May 2020, caregivers completed this online survey, including the Perceived Stress Scale. Participants (n = 335) were 99% female and mostly White (87%). Over half (60%) were breastfeeding, and 71% had a household income over CAD$60,000. Most participants (77%) received governmental parental benefits before the emergency, and 59% experienced no COVID‐19‐related economic changes. Over three quarters of participants (77%) scored moderate levels of perceived stress. Common themes of concern included social isolation, COVID‐19 infection (both caregiver and infant), and a lack of access to goods, namely, human milk substitutes ('infant formula'), and services, including health care, lactation support, and social supports. Most COVID‐19‐related information was sought from the internet and social media, so for broad reach, future evidence‐based information should be shared via online platforms. Although participants were experiencing moderate self‐perceived stress and shared numerous concerns, very few COVID‐19‐related changes to infant feeding were reported, and there were few differences by socio‐economic status, likely due to a strong economic safety net in this Canadian setting.